The emerging spectrum of exposure-related bronchiolitis. Issue 2 (April 2018) - Krefft, Silpa D.; Cool, Carlyne D.; Rose, Cecile S.
Abstract : Purpose of review: Exposure-related bronchiolitis is increasingly recognized as an important but challenging clinical diagnosis. Acute and chronic inhalational exposures are associated with variable clinical presentations and a spectrum of histopathologic abnormalities affecting the small airways. This review provides an overview of the histologic patterns and occupational settings for exposure-related bronchiolitis, along with recent advances in disease diagnosis and management. Recent findings: The entire histopathologic spectrum of bronchiolitis (constrictive, obliterative, proliferative, lymphocytic, respiratory) has been reported in exposure-related bronchiolitis. Recent studies have shown that lung clearance index testing and impulse oscillometry are more sensitive than spirometry in detecting small airways abnormalities and may augment the diagnosis of occupational bronchiolitis. Prognosis in indolent occupational bronchiolitis appears more favorable than some other types of bronchiolitis but is variable depending on the extent of bronchiolar inflammation and the stage of disease at which exposure removal occurs. Summary: No specific histopathologic pattern of bronchiolitis is pathognomonic for occupational bronchiolitis as one or more histologic patterns may be present. A high index of suspicion is needed for exposure and disease recognition. Recent advances that may aid in diagnosis include transbronchial cryobiopsy, lung clearance index testing, and impulse oscillometry, although further research is needed.